The relationship between antidepressants and breast cancer: evidence from Mendelian randomization - Dong Niu; Chenchen Li; Xiaoyu Yan; Haoran Qu; Yuling Zheng (Cancer Causes & Control, 2024)
Background The use of antidepressants has increased over the years, but the relationship between antidepressant use and the risk of breast cancer is not uniform because of confounding factors. We aimed to assess the effect of antidepressants on breast cancer risk using a two-sample Mendelian randomization (MR) approach.stet Methods Secondary data analysis was performed on pooled data from genome-wide association studies based on single-nucleotide polymorphisms that were highly correlated with antidepressants, SSRI drugs, and serotonin and prolactin levels were selected as instrumental variables to evaluate the association between antidepressants and SSRI drugs and prolactin levels with breast cancer and ER+/ER- breast cancer. We then performed a test of the hypothesis that SSRI drugs elevate prolactin concentrations. We performed two-sample Mendelian randomization analyses using inverse variance weighting, MR-Egger regression, and weighted median methods, respectively. Results There was no significant risk association between antidepressant and SSRI use and the development of breast cancer, ER-positive or ER-negative breast cancer ( P > 0.05), and serotonin concentration was not associated with breast cancer risk ( P > 0.05). There was a positive causal relationship between prolactin levels and breast cancer (IVW, P = 0.02, OR = 1.058) and ER-positive breast cancer (Weighted median, P = 0.043, OR = 1.141; IVW, P = 0.009, OR = 1.125). Results in SSRI medication and prolactin levels showed no association between SSRI analogs and prolactin levels ( P > 0.05). Conclusion Large MR analysis showed that antidepressants as well as SSRI drugs were not associated with breast cancer risk and the SSRI-prolactin-breast cancer hypothesis did not hold in our analysis.